Airborne Nicotine Concentrations in the Workplaces of Tobacco Farmers - Seok-Ju Yoo; Sung-Jun Park; Byoung-Seok Kim; Kwan Lee; Hyun-Sul Lim; Jik-Su Kim; In-Shik Kim (Korean Society for Preventive Medicine, 2014)
ObjectivesNicotine is a natural alkaloid and insecticide in tobacco leaves. Green tobacco sickness (GTS) is known as a disease of acute nicotine intoxication among tobacco farmers. Until now, GTS has been recognized globally as a disease that results from nicotine absorption through the skin. However, we assumed that GTS might also result from nicotine inhalation as well as absorption. We aimed to measure the airborne nicotine concentrations in various work environments of Korean tobacco farmers.MethodsWe measured the nicotine concentrations in the tobacco fields, private curing barns, and joint curing barns of farmers from July to October 2010. All sampling and analyses of airborne nicotine were conducted according to the National Institute for Occupational Safety and Health manual of analytic methods.ResultsThe airborne nicotine concentrations (geometric mean [geometric standard deviation]) in the tobacco field were 83.4 mg/m3 (1.2) in the upper region and 93.3 mg/m3 (1.2) in the lower region. In addition, the nicotine concentration by personal sampling was 150.1 mg/m3. Similarly, the nicotine concentrations in the private curing barn, workers in curing barns, the front yard of the curing barn, and in the joint curing barn were 323.7 mg/m3 (2.0), 121.0 mg/m3 (1.5), 73.7 mg/m3 (1.7), and 610.3 mg/m3 (1.0), respectively.ConclusionsThe nicotine concentration in the workplaces of tobacco farmers was very high. Future studies should measure the environmental concentration of nicotine that is inhaled by tobacco farmers.